Phytochemistry, allelopathy and anticancer potentiality of Withania somnifera (L.) Dunal (Solanaceae) - Ahmed,H. A. (2024)
Abstract Withania somnifera is a wild plant that shows great activity and safety against several human diseases. The current research explored the plant's chemical composition and allelopathic effects on Rumex dentatus (recipient plant). Moreover, anticancer activity is also tested against four types of human cancer cell lines. Chemical analysis of W. somnifera showed a high percentage of saponins and tannins, while glycosides, alkaloids, and flavonoids occurred in the second order. Results of the allelopathic experiments revealed significant inhibition of the R. dentatus plumule and radicle lengths as well as their relative dry weights. In addition, significant reductions in some primary metabolites of R. dentatus, like non-reducing and total sugar as well as soluble proteins, were determined. Cytotoxic potentiality of W. somnifera was also proved against four different cancer lines, namely; human hepatocellular carcinoma cell line (HepG2), human non-small cell lung cancer cell line (A549), human breast cancer cell line (MCF7), and colon cancer cell line (CaCo2) with IC50 value of about 38, 19, 27, and 24 g/ml, respectively.